Love Me, Love Me Not: The Counterintuitive Relationships in Social Networking Sites - Ramadan, Zahy (2024)
Brand connections are one of the key marketing fields that have seen growth through social networking sites (SNS). The literature agrees that SNS users have positive relationships with their favorite brands based on their experiences. However, such acceptance could be formed prematurely, because sometimes analysis of consumer relationships excludes the mediator position of the social network itself. This study seeks to examine the mediating role in consumer relationships between affective and cognitive customers and SNS. Semi-structured, in-depth interviews with 41 people were conducted to establish qualitative research designs. The results indicate a deep affective customer-SNS partnership, which implies that SNS consumers and brands work together in a counterintuitive way. The results suggest that while SNS are trusted and highly valued by users, they do not always support brands. This shows that close relationships with social platforms outweigh users’ relationship with other brands on these SNS platforms. This study shows that SNS have an interfering adverse impact on consumer-brand relationships within these platforms. The research discusses the counterintuitive influence of social platforms on consumer-brand relationships.